A New Approach for Estimating Insulation Condition of Field Transformers Using FRA - Yousof, Mohd Fairouz Mohd; Al-Ameri, Salem; Ahmad, Hussein; Illias, Hazlee Azil; Md Arshad, Syahrun Nizam (Stefan cel Mare University of Suceava, 2020)
Frequency response analysis (FRA) is a tool for evaluating mechanical integrity of transformer's core and winding. However, several studies have reported that FRA is also sensitive to other parameters such as temperature, moisture content and presence of oil. Since some of these parameters are critical in the insulation degradation process, it is interesting to further investigate the possibility of using FRA for insulation assessment. In this paper, the insulation conditions of three field transformers are investigated using FRA. This is performed after statistical analysis on the response suggested no mechanical damage on the transformers. The responses are further analyzed to determine the percentage of change of winding capacitance. This is achieved by comparing resonance frequencies between the responses. The percentage of change represents the amount of degradation in the insulation. This is because as the insulation condition degrades, the response is shifted towards lower frequencies. This new investigation demonstrates the applicability of FRA to estimate the insulation degradation. © 2020 AECE.